Embracing Sustainability: A New Paradigm for Healthcare Organizations Beyond Corporate Social Responsibility - Intissar Haddiya (Disease and Health Research: New Insights Vol. 6, 2024)
Corporate social responsibility (CSR) is a concept that has varied through history, with evolving definitions that aim to determine the interconnections between corporations and communities. CSR in healthcare services refers to the convergence of medicine supply facilities, nursing facilities, food supply facilities, ambulance service, and medical assistance that are stimulated by the undertaking of social responsibilities by hospitals and healthcare centres. Currently, in addition to ethics, this concept of social responsibility is increasingly considered in the context of healthcare delivery suggesting a new paradigm in hospital management. Healthcare organizations’ managers’ adherence to sustainability concepts is crucial to enable their implementation. Moreover, all hospital workers can also have a role to play, at various levels, according to their fields of action, as these concepts also refer to Bioethics principles, which are a combination of bioscience with humanistic knowledge, that have played a pivotal role in influencing policy changes in the last decades. Sustainability is another emerging strategic goal for healthcare systems and organizations. In this opinion paper, the application of social responsibility, sustainability and ethics to healthcare organizations have been discussed.